Energy optimised cryptography for low power devices in internet of things. (5th July 2019) - Rajesh, G.; Krishna, C. Vamsi; Selvaraj, B. Christopher; Karthik, S. Roshan; Sangaiah, Arun Kumar
Internet of things has a plethora of devices ranging from high capacity servers to low powered devices that works with Bluetooth, ZigBee, GPRS, RFID, Wi-Fi, etc. These low power devices are constrained to power management, reliability, security and privacy limitations. The existing traditional security algorithms could not be applied to these low power devices due to high processing and battery power requirements. Here, an energy optimised cryptography (EOC) for low power devices in IoT has been proposed. Here the security to low power devices has been accorded by two light weight security techniques called R2CV, a sub key generation method and optimised message authentication code generation function (OMGF) which maintain security without compromising energy consumption and processing power consumption. The proposed security algorithms reduce the computational requirements for sub key generation and MAC generation in low power devices. The experimental results are compared with existing algorithms like RC5 and SHA, and are proven that R2CV and OMGF reduce time consumption, increase battery life and in turn extend network lifetime.